Technology Integration in Arabic Language Skills Development in the Digital Era - Sarah, Sarah; Rizqia, Ana Sabila; Lisna, Lisna; Ali, Mad (Al-Fusha : Arabic Language Education Journal, 2024)
The development of methods and the use of technology in learning Arabic has become the focus of attention in the context of education. The purpose of this research is to provide a comprehensive understanding of learning methods and technology integration in teaching Arabic. The research method used is a literature study that reviews the development of literature related to classical and modern methods such as grammar-translation, direct, reading, and speech, as well as the application of technology such as audiovisual, e-learning, and games in the learning process. The results of the study show the obstacles in the application of methods and technologies, as well as the proposed innovative efforts to overcome these challenges. In conclusion, the development of Arabic learning methods and technologies remains relevant and sustainable in the digital era.